Design of a Web-Based Information System for the Registration and Numbering of Notarial and PPAT Deeds - Sitepu, Maulidya Hanifah; Budiarto, Eko; Afriantoro, Irfan (Jurnal Teknologi Informatika dan Komputer, 2026)
The rapid advancement of digital technology has transformed nearly every aspect of human life, exerting a substantial impact across multiple sectors, including communication, education, healthcare, and business. In the digital era, the utilization of information technology has become increasingly critical in notarial administration, particularly in the registration and numbering of Notarial and PPAT deeds.  Developments in information technology particularly in software and hardware have enabled process automation, rapid data processing, and improved accessibility of information. This study aims to design and develop a web-based information system for notary and PPAT deed numbering registers to replace the manual system. This system aims to improve data management efficiency, speed up searches, and improve the accuracy and consistency of register management. The method used is a qualitative approach with Agile methodology, with data collection through interviews, observation, and documentation studies. System development was carried out iteratively, with testing to ensure system functionality and reliability. The results of the study show that the developed system can manage data more efficiently, reduce manual errors, and improve data accessibility and security. This study concludes that the implementation of a web-based system can improve the efficiency and accuracy of data management, and recommends gradual implementation with a focus on testing and continuous maintenance.